2009
DOI: 10.1007/s10327-009-0199-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characteristics of Fusarium verticillioides from corn in the Philippines

Abstract: Fusarium verticillioides (teleomorph: Gibberella moniliformis = G. fujikuroi mating population A) is one of the most important fungal pathogens of corn worldwide. The pathogen produces fumonisins, mycotoxins that are potentially harmful to humans and animals. Thirty-five Fusarium isolates from Laguna and Isabela, Philippines were identified morphologically and molecularly as F. verticillioides and characterized by PCR for mating type (MAT). Twenty-six isolates were MAT1-2, while nine isolates were MAT1-1. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
0
14
1
Order By: Relevance
“…On the other hand, our results indicated that fumonisin production and disease did not seem to be directly related, similarly to F. proliferatum in wheat . However, in the case of F. verticillioides in maize, the evidence is contradictory, suggesting that the role of fumonisins is far from being understood and might depend on the host considered. Production of mycotoxins, including fumonisins, might aid in colonization of plant tissue and competition against other fungal species during infection, but their implication in bakanae disease symptoms is probably reduced.…”
Section: Discussioncontrasting
confidence: 56%
“…On the other hand, our results indicated that fumonisin production and disease did not seem to be directly related, similarly to F. proliferatum in wheat . However, in the case of F. verticillioides in maize, the evidence is contradictory, suggesting that the role of fumonisins is far from being understood and might depend on the host considered. Production of mycotoxins, including fumonisins, might aid in colonization of plant tissue and competition against other fungal species during infection, but their implication in bakanae disease symptoms is probably reduced.…”
Section: Discussioncontrasting
confidence: 56%
“…The experiment was evaluated 45 days after seed emergence. Root volume was measured according to Burdett ( 1979 ) and disease severity was evaluated as described in Cumagun et al ( 2009 ). An additional experiment was performed as a control to confirm that bacteria did not cause any detrimental effects to root volume; this experiment used a set of bacterial-treated seeds compared to an untreated seed control (receiving water) grown in sterile sand under the same conditions as listed above (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, isolates belonging to the new species grew considerably faster (10-17 mm/day) at 25°C than at 30°C (7-12 mm/day). When five isolates representing F. andiyazi and 10 isolates from the new Fusarium species were used to inoculate the stalks of mature sorghum plants using the toothpick inoculation method (Cumagun et al, 2009), all of them produced typical lesions that were absent in the control plants. This suggested the pathogenicity of both species to sorghum and proved that they were responsible for the stalk rot of sorghum.…”
Section: Morphological and Cultural Characterizationmentioning
confidence: 99%